Penggunaan Strategi Polya dalam Menyelesaikan Masalah Soal Cerita Volume Kubus dan Balok Di SD - Rosa, Dewi Yulia; Ahmad, Syafri; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study is aimed to  use  the Polya strategy to improve student learning outcomes in solving the word  problem  volume of cubes and beams in class V SD.The research subjects were 28 grade V students. The implementation is done in two cycles with the procedure consisting of planning, implementation, observation, and reflectoin The implementation is done in two cycles with the research procedure consist of planning, implementation, observation, and reflection.n. The results showed an increase from the results:  a) RPP I of the average cycle of 85.71% (B), cycle II 92.86% (A),  b) the implementation of aspects of the teacher the first cycle an average of 81.25% (B), and the second cycle 93.75% (A),  c) the implementation of the aspects of the first cycle students on average 78.12% (B), and the second cycle 93.75% (A),  d) results student learning cycle I average 75.52 and cycle II 89.37. The conclusion of the results of the study is that by using the policy strategy to improve student learning outcomes in solving the problem of the story problems of the volume of cubes and beams in class V SDN 07 Nan Sabaris. Keywords: Study Outcomes: word problem; Polya